Digest: Banding together to battle adversaries has its consequences*. (24th April 2019) - Sudianto, Edi
Abstract: Why did life evolve from single‐celled to multicellular organisms? Could there be advantages to this transition? What about associated fitness costs? Kapsetaki and West found that although multicellularity allows Chlorella sorokiniana to avoid predation from similarly‐sized predators, it also reduces their competitiveness when resources are limited.